Respons Generasi Z terhadap Konser Musik dalam Kampanye Politik 2024 - Khabibah, Shonia Ummu; Gunawan, Gunawan (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
This article explores music concerts as popular culture used for the 2024 Election political campaign in Semarang. The background of the article is that music concerts are a form of popular culture that is close to generation Z, which is being used by presidential candidate pairs for the 2024 election as a political tool to attract the sympathy of generation Z because generation Z dominates the voter list for the 2024 election. The focus of this article is on music concerts for political campaigns which was held in Semarang. Data collection in this paper applies qualitative methods. The findings in this paper show that music concerts for political campaigns have become popular culture that suits the character of generation Z. Each pair of candidates tries to attract the votes of generation Z through these music concerts. By bringing the character closer to generation Z, namely choosing bands and singers who are invited as representatives of the values ​​and identity held by generation Z. However, this causes cultural reification because generation Z does invoive to the political goals of the campaign and is more prioritize watching their favorite bands and singers. Thus, efforts to attract the votes of generation Z become ineffective because the political objectives of the campaign are sidelined by the interests of generation Z in seeking entertainment. However, popular culture, politics and generation Z are three things that are interconnected and become an important part of the 2024 political campaign. Music, which previously functioned as entertainment and art, has turned into a political stage for candidates to attract votes from Generation Z.